Parables for the virtual : movement, affect, sensation - Massumi, Brian (Post-contemporary interventions., 2021)
"This twentieth anniversary edition of Brian Massumi's pioneering and highly influential Parables for the Virtual includes a significant new preface that situates the book in relation to developments since its first publication and outlines the evolution of its main concepts."--